Index of mechanical efficiency in competitive and recreational long distance runners - McBride, J. M.; Davis, J. A.; Alley, J. R.; Knorr, D. P.; Goodman, C. L.; Snyder, J. G.; Battista, R. A. (Journal of Sports Sciences, 2015)
The purpose of this investigation was to compare external work and net energy expenditure during a bout of repetitive stretch-shortening cycles between competitive and recreational long-distance runners. Participants were divided into either competitive or recreational runners based on their maximal oxygen consumption and self-reported 1600 m times. The stretch-shortening cycle involved a repetitive hopping protocol on a force plate while measuring oxygen consumption and lactate accumulation for a total of 10 min. External work and net energy expenditure were calculated for 3 min after steady state was achieved and the ratio between these variables was utilised as an index of mechanical efficiency. Lower extremity stiffness was calculated during this interval as well. Net energy expenditure was significantly lower in competitive runners (152.6 ± 33.3 kJ) in comparison to recreational runners (200.6 ± 41.4 kJ) (P = 0.02) given similar amounts of external work performed in both groups (competitive runners = 65.6 ± 20.1 kJ, recreational runners = 68.8 ± 12.1 kJ) (P = 0.67). Index of mechanical efficiency was significantly different between competitive runners (43.2 ± 9.0%) and recreational runners (34.8 ± 5.3%) (P = 0.03). No significant differences were found in lower extremity stiffness (P = 0.64). Competitive distance runners can perform similar levels of external work with lower net energy expenditure and thus a higher index of mechanical efficiency during repetitive stretch-shortening cycles in comparison to recreational runners with similar values of lower extremity stiffness. This ability could possibly be due differences in muscle-tendon length changes, muscle pre-activation, cross-bridge potentiation and short-latency reflex responses as a result of training which should be considered for future investigation.